Food adulterations - Peck, Ella Emerson (My University, 1899)
Introduction: The subject, Food Adulterations is in reality a very serious one from one point of view, and should be very carefully investigated. But adulteration is not carried on to such an extent as is generally supposed. The majority of the people seem to think that the rare thing is getting food that is not adulterated. This is humorously expressed by a little poem written by Robert J. Burdette which reads as follows: Placid I am, content, serene I take my slab of gypsum bread, And chunks of oleomargarine Upon its tasteless sides were spread. The egg I eat was never laid By any cackling, feathered hen, But from the Lord knows what ‘tis made In Newark by unfeathered men. I wash my simple breakfast down with fragrant chicory so sweet Or with the best black tea in town- Dried willow leaves-I calmly sleep.
Citation: Peck, Ella Emerson. Food adulterations. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Harm of Adulterations; Why Adulteration Is Used; Detecting Adulteration; Theses; Manuscripts (documents)